Scripting the mechanics of the benchmark manipulation corporate scandals: The ‘guardian' paradox - Jordanoska, Aleksandra (European journal of criminology, 2020)
This article implements a crime script analysis to understand the procedural dynamics of corporate benchmark-rigging in the financial services industry. In 2012 several global banks were implicated in the manipulation of various trading benchmarks, portraying the industry as affected by serious, pervasive and ‘organized' corporate crimes. Yet their dynamics have been relatively little studied by criminologists. To address this gap, we analyse official enforcement documentation, supplemented with data from interviews with key informants in the UK financial markets. We analyse the range of interactions between the relevant actors, their actions and the resources essential to the manipulations, and deconstruct the benchmark manipulations into four scenes (calculated positioning and identification of co-collaborators; recruitment; (ephemeral) manipulation; recompense and solicitation). The analysis reveals that regulatory and organizational systems play a paradoxical role of both ‘capable guardians' and ‘facilitators of misconduct'; this has implications for criminological theory.